Gradient Heatmetry in a Burners Adjustment - Pavel G. Bobylev; Andrey V. Pavlov; Vyacheslav M. Proskurin; Yuriy V. Andreyev; Vladimir Yu. Mityakov; Sergey Z. Sapozhnikov (Inventions, 2022)
Measuring the heat flux in the furnace of industrial boilers is an urgent task in the power industry. Installing the measuring instruments directly into the furnace is a laborious and complex process. It requires a complete shutdown of the boiler, which incurs economic costs. It is most efficient to use portable probes with measuring insert. The created cooled probe with a heterogeneous gradient heat flux sensor is a unique and versatile tool that allows for the configuration and control of the operation of power boilers. This article compares experimental values with calculation methods. The obtained heat flux per unit area is in good agreement with the theoretical concepts when the values are averaged. The technique used in this paper makese it possible to determine the maximum heat-stressed zones and areas with stable or unstable combustion. The main combustion zones that are typical for the flaring of any fuel are identified. This approach allows us to consider various approaches to heat transfer enhancement during the combustion of both liquid and gaseous fuels. Comparison of experimental results with the data of other authors is not quite exact due to the complexity of the experiment. The study of burners in this configuration has not previously been considered in the literature.